Comparison of rowing performance improvements following various high-intensity interval trainings - Akca, F.; Aras, D. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to examine the effects of high-intensity interval training (HIT) and supramaximal interval training (SMIT) on indoor rowing performance; 20 male lightweight collegiate rowers (age = 21.77 ± 2.35 years, height = 178.4 ± 6 cm, body mass = 69.6 ± 3.1 kg) participated in this study. Baseline testing involved a 2,000-m time trial and incremental exercise test to determine VO2peak, peak power output (PPO), and power at 4 mmol/L blood lactate threshold. After the baseline tests, participants were allocated to SMIT or HIT intervention groups, which they performed 8 times over a 4-week period (2 times per week, 2 days apart). The SMIT involved 10 × 30-second intervals at 150% of the PPO with 4-minute rest. The HIT involved 8 × 2.5-minute intervals at 90% of the PPO with 3-minute rest. Of note, 5.7 and 5 seconds of improvements were observed in 2,000-m performance after SMIT and HIT interventions, respectively. Of note, 2,000-m time trial performance, 2,000-m power, PPO, relative, and absolute VO2peak were significantly improved after both training interventions. However, the differences between the groups were not significant. As a result, 4 weeks of SMIT improves 2,000-m rowing ergometer performance and related physiological variables in a similar fashion with HIT in collegiate rowers.